Cutaneous histiocytic sarcoma arising from soft tissue filler injections: a case report - Choi, Jangyoun; Park, Heeyang; Ko, Eun Jeong; Choi, Jong Yun; Moon, Suk-Ho; Oh, Deuk Young; Jun, Young-Joon (Frontiers in Oncology, 2025)
BackgroundThe administration of soft-tissue fillers is a popular aesthetic procedure. Nonetheless, it can result in complications such as foreign-body reactions, infections, skin necrosis, granulomas, and even malignant transformation. This case study documents an unusual occurrence of sarcoma following a prior cosmetic injection.Case reportA male patient, aged 76, presented with facial swelling. He received filler injections from a non-professional aesthetician twenty-five years ago. The patient reported a slow downward movement of the injected material, recurring inflammation, and the development of multiple nodules. An excisional biopsy and tissue culture were conducted, which did not identify any microorganisms but did reveal a dense infiltration of large polygonal cells with pleomorphic nuclei. The diagnosis of histiocytic sarcoma(HS) was confirmed through immunohistochemistry. A comprehensive systemic examination, including contrast MRI and PET-CT, identified multiple nodular soft tissue lesions in the subcutaneous layer of the face and intense metabolic activity in the same nodular lesions. Metabolic activities were also observed in the abdominal wall, indicating a potential migration of the injected material. Following diagnosis, all remaining lesions in the forehead, nose, and abdomen were surgically excised. Due to the complete nature of the excision, adjuvant chemoradiation was not administered.ConclusionThis case underscores the serious complication that can result from unauthorized filler injections, including the extremely rare histiocytic sarcoma. It emphasizes the necessity of cautious follow-up and patient education in aesthetic procedures.